2011
DOI: 10.1109/tbme.2011.2158605
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Multiscale Modeling of the Nervous System: Predicting Changes in Hippocampal Network Activity by a Positive AMPA Receptor Modulator

Abstract: One of the fundamental characteristics of the brain is its hierarchical organization. Scales in both space and time that must be considered when integrating across hierarchies of the nervous system are sufficiently great as to have impeded the development of routine multilevel modeling methodologies. Complex molecular interactions at the level of receptors and channels regulate activity at the level of neurons; interactions between multiple populations of neurons ultimately give rise to complex neural systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…We present the results for one vesicle release in Figure 9A, where it is clear that the current responses from both theoretical models are almost identical, although they have faster rise and decay times than the superimposed experimental results from reference [30]. All parameters for our AMPA receptor model and diffusion algorithm were optimized [19] with respect to experimental results from reference [23], and the differences observed in Figure 9A are likely due to limitations in experimental recording and dendritic integration, whereby membrane capacitance slows the response. Furthermore, the kinetic rate constants have not been optimized to fit the experimental data, which can dramatically affect the time series.…”
Section: Comparison To Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We present the results for one vesicle release in Figure 9A, where it is clear that the current responses from both theoretical models are almost identical, although they have faster rise and decay times than the superimposed experimental results from reference [30]. All parameters for our AMPA receptor model and diffusion algorithm were optimized [19] with respect to experimental results from reference [23], and the differences observed in Figure 9A are likely due to limitations in experimental recording and dendritic integration, whereby membrane capacitance slows the response. Furthermore, the kinetic rate constants have not been optimized to fit the experimental data, which can dramatically affect the time series.…”
Section: Comparison To Experimental Resultsmentioning
confidence: 99%
“…The parameters for the model given in Table 1 were adapted from the original values used in Robert and Howe [17] to additionally fit the experimental results from Kessler et al [23]. This optimization was presented in Bouteiller et al [19]. We write the coupled rate equations associated with the kinetic schemes as follows: …”
Section: Glutamate-ampa Receptor Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…More spatial scales can be integrated as well, including smaller scales down to the molecular level for describing the synapses and channel mechanisms with even higher complexity. It has been shown that small changes at the molecular level can have an impact on the neural-level reaction to electrical activity [12]. Through these modifications, a highly accurate model for studying many different research topics involving circuitry in the retina may be studied.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic models in the EONS platform used for training the functional model include neurotransmitter diffusion [9], the 16 state AMPA receptor model developed by Robert and Howe [10] and the 8 state NMDA receptor model by [11]. For more details on the EONS/RHENOMS synaptic platform please see [12] and [13]. …”
Section: Methodsmentioning
confidence: 99%